Representation and Commodification of Muslim Identity Through Halal Food Content by Influencer in Instagram - Dite Nursyamsi Mahmutami; Maria Regina Widhiasti (Universitas Cokroaminoto Palopo, 2026)
Instagram is one of the spaces used by influencers to influence their followers’ perception of certain ideologies and lifestyles, includes halal lifestyle. This study aims to analyze halal lifestyle represented and commodified by halal influencers through halal food content. One of the lifestyles that is also promoted by Instagram is halal lifestyle, which represented by Dian Widayanti dan Anca Syah among others through accounts @dianwidayanti and @anca.id. These two halal lifestyle influencers use Instagram to inform and educate their followers about halal food through the contents they produce. Using Krippendorff (2019) content analysis method, this study analyzed the contents of the influencers to show the representation of halal lifestyles on Instagram in the halal food content uploaded during November 2024 – April 2025. The results interpretation analysis uses the representation theory of Stuart Hall (1997), the commodification of Arjun Appadurai (2013) and the symbolic authority of Pierre Bourdieu (1991). This study shows @dianwidayanti and @anca.id using halal concept and differences in persona representation such as appearance, communication style and content narration as a branding strategy and reveals the commodification of religion through the capitalization of religious identity that occurs in the halal industry. The practices of representation and commodification construct religious authority through symbolic power in the public sphere and halal industrial world in Indonesia.